2007
DOI: 10.1143/jjap.46.3573
|View full text |Cite
|
Sign up to set email alerts
|

Emission Properties of Compact Antenna-Excited Super-High Pressure Mercury Microwave Discharge Lamps

Abstract: A compact high-intensity microwave discharge lamp and ignition system have been investigated using a couple of antennas and a solid-state microwave generator. It is found that the antenna-excited microwave discharge lamps can sustain mercury discharges at pressures higher than 100 atm with 2.45 GHz microwave power lower than 80 W, and that a stable plasma column is generated isolated from the lamp wall. The radial radiant profile is much different from that of conventional microwave discharge lamps without ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…These experiments have been carried out using high-pressure metal-halide lamps [1][2][3][4] and extremely high-pressure mercury discharge lamps. 5,6) The results showed stable high-pressure microwave discharges confined to the antenna gap because of efficient microwave power supply into the discharge space of the lamp using small antenna gap effects. Antenna-excited microwave discharge is called AEMD hereafter.…”
Section: Introductionmentioning
confidence: 97%
“…These experiments have been carried out using high-pressure metal-halide lamps [1][2][3][4] and extremely high-pressure mercury discharge lamps. 5,6) The results showed stable high-pressure microwave discharges confined to the antenna gap because of efficient microwave power supply into the discharge space of the lamp using small antenna gap effects. Antenna-excited microwave discharge is called AEMD hereafter.…”
Section: Introductionmentioning
confidence: 97%
“…12) Mizojiri et al reported APMP production using an antenna where plasma is produced on the tip of wire. 13) By combining a waveguide and a tube, a microwave torch using He has also been produced. 14,15) Another way to produce the APMP is the use of a discharge gap.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, 4) we demonstrated that the AEMD lamp could sustain mercury discharge at a pressure of around 100 atm using 2.45 GHz microwave power at a power of lower than 80 W. Therefore, the AEMD lamp ignition system is suitable as a light source for data projectors and many other lighting systems. Khan et al 6,7) have fabricated two types of miniaturized high-intensity discharge lamps using the techniques of micromachining and ICs.…”
Section: Introductionmentioning
confidence: 99%
“…A lamp ignition system for compact high-intensity discharge lamps has been investigated by our group [1][2][3][4][5] by applying the antenna effect to feed microwave power into high-pressure discharge lamps. The ignition system simply consists of a pair of antennas installed on compact discharge lamps and a solid-state microwave generator (SPC Electronics ESG-2450S-2A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation